ESTUDOS TAXONÔMICOS DE UMA ESPÉCIE DE TRICHOMYCTERIDAE (SILURIFORMES) NA BACIA DO RIO IVINHEMA, ALTO RIO PARANÁ - DONI, Giovanna Lôbo; DAGOSTA, Fernando César Paiva; DONIN, Laura Modesti; SÚAREZ, Yzel Rondon (ANAIS DO ENIC, 2025)
-